Insights from sociolinguistics and translation studies for maintaining bilingualism in the home - Ezhevskaya, Anya (Missiology, 2020)
The question of language maintenance often arises in multilingual families, be it missionary families returning to the sending country or those that have moved permanently to start a new life. Parents committed to preserving the benefits their children have as bilinguals may struggle to maintain a vibrant knowledge of their children’s first language as the family enters a new linguistic environment. To support such parents and other individuals seeking to preserve bilingualism in the home and in the immediate community, this article offers insights from related linguistic fields. The author draws on personal experience, as well as translation studies and the concept of language planning from sociolinguistics, to examine techniques to keep the language in question active.